Anthracyclines disaggregate and restore mutant p63 function: a potential therapeutic approach for AEC syndrome - Fabiana Boncimino; Ludovica D’Auria; Kristina Todorova; Sabina Y. van der Zanden; Jacques Neefjes; Anna Mandinova; Caterina Missero; Stefano Sol (Cell Death Discovery)
Abstract Ankyloblepharon-Ectodermal Defects-Cleft Lip/Palate (AEC) syndrome is a rare genetic disorder caused by mutations in the TP63 gene, which encodes a transcription factor essential for epidermal gene expression. A key feature of AEC syndrome is chronic skin erosion, for which no effective treatment currently exists. Our previous studies demonstrated that mutations associated with AEC syndrome lead to p63 protein misfolding and aggregation, exerting a dominant-negative effect. By performing a high-throughput screening of epigenetic and FDA-approved compounds in a co-transfection model of wild-type and mutant p63, we found that two compounds, Doxorubicin and Epirubicin, alleviate protein aggregation and restore p63 transactivation function. Moreover, treatment with these compounds reduced protein aggregation and restored the expression of keratinocyte-specific p63 target genes in primary keratinocytes derived from a conditional ΔNp63αL514F knock-in AEC mouse model, which mimics the ectodermal defects and skin erosions characteristic of AEC syndrome. A chemical analog of Doxorubicin, diMe-Doxorubicin, which exhibits lower tissue and organ toxicity, was also found to be effective in promoting the disaggregation of mutant p63 and rescuing its transcriptional activity. Our findings identify compounds that can partially resolve mutant p63 aggregation, increase its monomeric isoform, and reactivate its transcriptional function. These results suggest potential therapeutic efficacy for treating skin erosions in AEC syndrome.